2017
DOI: 10.1039/c7fo01383c
|View full text |Cite
|
Sign up to set email alerts
|

A combination of quercetin and resveratrol reduces obesity in high-fat diet-fed rats by modulation of gut microbiota

Abstract: Resveratrol and quercetin, widely found in foods and vegetables, are plant polyphenols reported to have a wide range of biological activities. Despite their limited bioavailabilities, both resveratrol and quercetin are known to exhibit anti-inflammation and anti-obesity effects. We hypothesized that gut microbiota may be a potential target for resveratrol and quercetin to prevent the development of obesity. The aim of this research was to confirm whether a combination of quercetin and resveratrol (CQR) could r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
217
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(260 citation statements)
references
References 61 publications
39
217
1
3
Order By: Relevance
“…At the genus level, our results reflected that the relative abundances of Bifidobacterium, Bacteroides, Alistipes, Lachnospiraceae NK4A136 group and Alloprevotella decreased while that of Parabacteroides, Eubacterium xylanophilum group, GCA-900066575, Lachnoclostridium, Lachnospiraceae UCG-006 and Romboutsia increased in the HFD group compared with the control group. In line with our results, earlier studies found that the abundances of Bifidobacterium (Zhu et al, 2018), Bacteroides (Zhang et al, 2015;Martinez et al, 2017), Alistipes (Zhu et al, 2018), Lachnospiraceae NK4A136 group , and Alloprevotella were negatively correlated with obesity, and the abundances of Parabacteroides (Lieber et al, 2018;Zhao et al, 2018), Eubacterium xylanophilum group , GCA-900066575 , Lachnoclostridium (Zhao et al, 2017b), Lachnospiraceae UCG-006 (Kang et al, 2019), and Romboutsia (Zhao et al, 2018) were positively correlated with obesity. Bifidobacterium, a beneficial microbial species, producing lactic acid and acetic acid, can reduce intestinal pH and inhibit the growth of various detrimental bacteria to maintain intestinal health (Wang R. et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…At the genus level, our results reflected that the relative abundances of Bifidobacterium, Bacteroides, Alistipes, Lachnospiraceae NK4A136 group and Alloprevotella decreased while that of Parabacteroides, Eubacterium xylanophilum group, GCA-900066575, Lachnoclostridium, Lachnospiraceae UCG-006 and Romboutsia increased in the HFD group compared with the control group. In line with our results, earlier studies found that the abundances of Bifidobacterium (Zhu et al, 2018), Bacteroides (Zhang et al, 2015;Martinez et al, 2017), Alistipes (Zhu et al, 2018), Lachnospiraceae NK4A136 group , and Alloprevotella were negatively correlated with obesity, and the abundances of Parabacteroides (Lieber et al, 2018;Zhao et al, 2018), Eubacterium xylanophilum group , GCA-900066575 , Lachnoclostridium (Zhao et al, 2017b), Lachnospiraceae UCG-006 (Kang et al, 2019), and Romboutsia (Zhao et al, 2018) were positively correlated with obesity. Bifidobacterium, a beneficial microbial species, producing lactic acid and acetic acid, can reduce intestinal pH and inhibit the growth of various detrimental bacteria to maintain intestinal health (Wang R. et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the apparent changes of inflammatory cytokine and gut microbiota, we observed some key communities associated with IL‐6 and TNF‐α in the present study. In our system, Christensenellaceae and Bacteroidales reported negative correlations to IL‐6 and TNF‐α, which was supported by the previous study . Some pathogenic bacteria including Streptococcus and Veillonella increased levels of the cytokines IL‐8, IL‐6, IL‐10, and TNF‐α .…”
Section: Discussionsupporting
confidence: 90%
“…Changes in the composition of gut microbiota are associated with inflammation in HFD‐induced obesity and diabetes in mice . Quercetin and resveratrol reduced serum lipids and attenuated serum inflammatory cytokines IL‐6 and TNF‐α through restoring gut microbiota dysbiosis induced by a HFD in Wistar rats . In addition to the apparent changes of inflammatory cytokine and gut microbiota, we observed some key communities associated with IL‐6 and TNF‐α in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…The effect of ω‐3 PUFAs on the microbiome was assessed by comparing specific bacteria using LEfSe analysis. Our results showed that gut microbiota of ZT0CON group was mainly associated with increased levels of SCFAs producing bacteria compared with the other three groups at ZT0, including Ruminococcaceae ( unidentified_Ruminococcaceae , Ruminiclostridium_9 , and Ruminiclostridium_1 ) and Butyrivibrio . SCFAs, including acetate, propionate, and butyrate, are the primary end products from the degradation of carbohydrates by gut microbiota in the intestine and could regulate obesity and obesity‐related disturbances in glucose metabolism and insulin resistance .…”
Section: Discussionmentioning
confidence: 66%